Factors impacting the use of antenatal care and hospital child delivery services: a case study of rural residents in the Enshi Autonomous Prefecture, Hubei Province, China. (21st January 2014) - Zhang, Yin; Chen, Minxing; Lu, Jun; Hao, Mo; Zhang, Changli; Sun, Mei; Li, Xiaohong; Chang, Fengshui
Summary: This study was undertaken to understand the factors that impact whether rural women obtain antenatal care (ANC) and choose to use hospital delivery services in central and western China. We chose to conduct field research with the rural residents in Hubei Province through a combination of random sampling and purposive sampling methods. A mixed method approach was taken to analyze the factors impacting the use of ANC and hospital delivery services from the perspective of the villagers. Our results indicate that the quality of the available ANC services is poor. In particular, women who have special circumstances and unplanned pregnancies or who become pregnant prior to marriage are confronted with inadequate ANC and hospital child delivery services. The factors that impact whether women use or not use ANC and hospital delivery services and that cause women to choose hospital or home delivery can be understood at three levels: macro, middle, and micro. We strongly suggest that the policies and projects that promote maternal healthcare in rural areas be sustained with an added focus on including women with special circumstances. Village doctors can be enlisted to regularly visit pregnant women at home and to provide extra explanation about the ANC services available and the purpose of maternal healthcare. These findings and suggestions can be used by local health providers and decision‐makers to improve the quality of ANC and hospital delivery services. Copyright © 2014 John Wiley & Sons, Ltd.